2018
DOI: 10.1161/circimaging.117.006894
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Right Ventricular Dysfunction in Heart Failure With Reduced Ejection Fraction

Abstract: Background-In heart failure (HF) with reduced ejection fraction, right ventricular (RV) impairment, as defined by reduced tricuspid annular plane systolic excursion, is a predictor of poor outcome. However, peak longitudinal strain of RV free wall (RVFWS) has been recently proposed as a more accurate and sensitive tool to evaluate RV function. Accordingly, we investigated whether RVFWS could help refine prognosis of patients with HF with reduced ejection fraction in whom tricuspid annular plane systolic excurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(71 citation statements)
references
References 34 publications
(57 reference statements)
5
50
0
3
Order By: Relevance
“…The presence of RV dysfunction is unequivocally associated with worse outcomes. Carluccio et al investigated and followed up 200 patients with HFrEF but normal TAPSE [ 40 ]. RV free wall strain provided incremental prognostic value compared to the conventional measurement.…”
Section: Heart Failure With Preserved and Reduced Left Ventricular Ejmentioning
confidence: 99%
“…The presence of RV dysfunction is unequivocally associated with worse outcomes. Carluccio et al investigated and followed up 200 patients with HFrEF but normal TAPSE [ 40 ]. RV free wall strain provided incremental prognostic value compared to the conventional measurement.…”
Section: Heart Failure With Preserved and Reduced Left Ventricular Ejmentioning
confidence: 99%
“…RV-GLS showed a slightly greater prognostic power, probably due to the effect of systolic interventricular dependence, which greatly contributes to RV longitudinal shortening [30]. In addition, further studies have demonstrated the independent and incremental prognostic value of strain measures [32,33], even in patients who have undergone cardiac resynchronization therapy (CRT) [34], and in those with normal TAPSE [35]. These findings strengthen the clinical usefulness of these parameters in routine clinical practice.…”
Section: Strain and Strain Rate Imagingmentioning
confidence: 61%
“…Using 2D spackle tracking, the longitudinal strain can be derived in all RV segments. This measure correlates well with the RV ejection fraction by CMR (74) and has been validated in patients with various cardiovascular conditions (75,76) Recent studies have confirmed the high sensitivity of RV strain for the identification of RV dysfunction in the context of severe TR (77,78). The right ventricular change in pressure over time (dP/dT), as assessed by echocardiography has been proposed as a novel parameter reflecting RV contractility and correlates well with CMR RV ejection fraction (77)(78)(79).…”
Section: Assessment Of the Right Ventricular Functionmentioning
confidence: 87%